Efforts To Build The Image Of Jambi University Library Through The Development Of An Innovative-Realistic Service Model Based On Entrepreneurship (Irbe Model) - Zurweni, Zurweni; Malik, Affan (Publikasi Indonesia, 2024)
This research is through the development of an Innovative-Realistic Service Model based on entrepreneurship that is relevant to the demands of the industrial revolution era 4.0 embedding intelligent technology that can be connected to various fields of human life. The challenge in the future is to strive to improve the service skills of librarians and library staff in all fields by always innovating by animating an entrepreneurial attitude. This research explores the importance of improving the quality of UPT Jambi University Library as an information center in the millennial era. This research aims to build the image of UPT Library Jambi University by improving service quality to become more charismatic and quality. In the context of the industrial revolution 4.0, this research develops an Innovative-Realistic Service Model Based on Entrepreneurship (IRBE) that combines smart technology and entrepreneurial attitudes. By using the Research & Development method and adapting the ASSURE model, this research creates a model that suits the needs of UPT Jambi University Library. Although the initial response from users indicated suboptimal service quality, the IRBE Model received a feasibility percentage of 88.85%, indicating the potential for effective implementation. This model emphasizes reality and adaptability to the actual situation and conditions at Jambi University. However, there is a need to improve entrepreneurial attitudes and skills in its implementation in the future. Furthermore, this study suggests the implementation of the IRBE Model in UPT Library of Jambi University and similar institutions, as well as further research for optimization of the model.